2000
DOI: 10.1046/j.1524-475x.2000.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and chemokine receptor expression in keloid and normal fibroblasts

Abstract: Keloids are benign collagenous tumors that occur during dermal wound healing in genetically predisposed individuals. The lesions are characterized by over-proliferation of fibroblasts, some leukocyte infiltration, and prolonged high rates of collagen synthesis. To determine whether leukocyte chemoattractants or chemokines are participating in this disease process, immunohistochemical staining for the CXC chemokine, MGSA/GRO␣, and its receptor, CXCR2, was performed on tissue from keloids, hypertrophic scars and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Our results also showed that the changes of DARC in keloid fibroblasts were not related to fibroblast proliferation. However, in line with a previous study (Nirodi et al, 2011), wound closure was significantly slower in injured keloid fibroblasts than in normal fibroblasts. When DARC was interrupted, the migration of keloid fibroblasts was promoted.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results also showed that the changes of DARC in keloid fibroblasts were not related to fibroblast proliferation. However, in line with a previous study (Nirodi et al, 2011), wound closure was significantly slower in injured keloid fibroblasts than in normal fibroblasts. When DARC was interrupted, the migration of keloid fibroblasts was promoted.…”
Section: Discussionsupporting
confidence: 91%
“…In humans, CCL2 is a major factor in progressive renal fibrosis, ischemic cardiomyopathy, atherosclerosis, and pancreatitis (Tesch, 2008;Xia and Frangogiannis, 2007;Marra, 2005), which can stimulate the expression of fibroblast collagen (van Horssen et al, 2006). Moreover, the enhancement of CCL2 and CCR2 has also been reported in keloid tissues, augmenting the fibroblast proliferation (Nirodi et al, 2011). CXCL8 is another important chemokine mediating inflammation, which is assumed to be the macrophage-derived mediator of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keloids are fibrous overgrowths at sites of cutaneous injury that form as a result of an abnormal wound-healing process in genetically susceptible individuals 12,13 and, unlike normal scars, do not regress. 6,14,15 Keloid disease is a benign dermal fibroproliferative tumor unique to humans 6,14 -16 that never becomes malignant.…”
Section: Clinical and Morphologic Differentiationmentioning
confidence: 99%
“…Surgical scars are not only a cosmetic concern but they can also cause a number of side effects including pain, itching, discomfort, contracture, and other functional impairment [1,2]. Any patient may develop keloids, but dark skinned ethnicities are more susceptible to keloid formation with upwards of 15% of the population at a heightened risk [3][4][5][6][7]. However, keloids have still not a definitive therapy.…”
Section: Introductionmentioning
confidence: 99%